Beyond markedness in formal phonology - Samuels, Bridget D. (Linguistik Aktuell/Linguistics Today Ser., 2017)
"In recent years, an increasing number of linguists have re-examined the question of whether markedness has explanatory power, or whether it is a phenomenon that begs explanation itself. This volume brings together a collection of articles with a broad range of critical viewpoints on the notion of markedness in phonological theory. The contributions span a variety of phonological frameworks and relate to morphosyntax, historical linguistics, neurolinguistics, biolinguistics, and language typology. This volume will be of particular interest to phonologists of both synchronic and diachronic persuasions, and has strong implications for the architecture of grammar with respect to phonology and its interfaces with morphosyntax and phonetics"--